2008
DOI: 10.1080/00754170802472885
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite therapy with older children: mutuality in the relationship of a parent–child attachment

Abstract: This is the last of a series of three papers exploring the use with older children of tripartite psychotherapy -a technique of psychoanalytic psychotherapy of the parent-child relationship with both parent and child in the room together with the therapist. Tripartite psychotherapy merits more attention than it has received. It is a flexible, psychoanalytically oriented approach to parent-child relationship problems, particularly useful when the primary attachment has gone awry. A study is presented of a mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These children may also have better sibling relationships, more positive self-esteem, an increased sense of hopefulness, greater trust in people and relationships, and heightened optimism about their future compared to children with insecure attachment styles. In contrast, insecure and disorganised attachment styles in infancy have been associated with elevated rates of emotional, social and behavioral disturbances in infancy, toddlerhood, preschool and beyond ( Van Ijzendoorn et al, 1999 ; Granot and Mayseless, 2001 ; Sroufe, 2005 ; Berlin, 2008 ; Fearon et al, 2010 ; Madigan et al, 2013 ). A 30-year prospective study of infants with insecure attachment styles at 8 months of age, found insecure attachment to be associated with a higher risk of mental health concerns at 30 years of age ( Fan et al, 2014 ).…”
Section: Attachment and Mentalizationmentioning
confidence: 99%
“…These children may also have better sibling relationships, more positive self-esteem, an increased sense of hopefulness, greater trust in people and relationships, and heightened optimism about their future compared to children with insecure attachment styles. In contrast, insecure and disorganised attachment styles in infancy have been associated with elevated rates of emotional, social and behavioral disturbances in infancy, toddlerhood, preschool and beyond ( Van Ijzendoorn et al, 1999 ; Granot and Mayseless, 2001 ; Sroufe, 2005 ; Berlin, 2008 ; Fearon et al, 2010 ; Madigan et al, 2013 ). A 30-year prospective study of infants with insecure attachment styles at 8 months of age, found insecure attachment to be associated with a higher risk of mental health concerns at 30 years of age ( Fan et al, 2014 ).…”
Section: Attachment and Mentalizationmentioning
confidence: 99%
“…Psychoanalytically-oriented parent-infant/child psychotherapy may be variously named elsewhere -Watch Wait and Wonder (Cohen et al 1999), child-parent psychotherapy (Lieberman 2004), parent-infant psychotherapy (Baradon et al 2005), tripartite psychotherapy (Berlin 2008), under fives counselling (Emanuel and Bradley 2008) -but key to all approaches (as indicated by the author's preferred term "parent-infant/child psychotherapy") is targeting parent(s) together with child. Interventions may shift from orienting treatment towards the child or towards the parent; invariably, however, the parent(s) and infant/child attend sessions together.…”
Section: Introductionmentioning
confidence: 99%